NEW UKRAINIAN SCHOOL: AI IMPLEMENTATION IN EDUCATION - Iryna Nikitina; Tetyana Ishchenko (Scientific Journal of Polonia University, 2025)
The New Ukrainian School reform aims to modernize education. This article explores the potential of Artificial Intelligence (AI) to enhance this initiative. It discusses ways to integrate artificial intelligence into the Ukrainian education system to modernize learning and teaching processes. It highlights key reforms of the Ukrainian New School and presents initiatives such as personalized learning tools, automated assessment systems to improve student performance and optimize teachers' workload. The article also highlights the role of technology and discusses the issues of gradation of AI use in the classroom. Successful AI implementation requires careful planning, collaboration, and a focus on student needs. The article emphasizes the importance of embracing AI responsibly to create a more equitable and effective education system for all Ukrainian students. The authors present the features of the current state of Ukrainian education and the ways of its development. This approach reflects Ukraine's commitment to creating a progressive, inclusive and technology-oriented educational environment.